2000
DOI: 10.1200/jco.2000.18.8.1606
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Chemotherapy and Pelvic Radiation Therapy Compared With Pelvic Radiation Therapy Alone as Adjuvant Therapy After Radical Surgery in High-Risk Early-Stage Cancer of the Cervix

Abstract: The addition of concurrent cisplatin-based CT to RT significantly improves progression-free and overall survival for high-risk, early-stage patients who undergo radical hysterectomy and pelvic lymphadenectomy for carcinoma of the cervix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
527
3
8

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,964 publications
(604 citation statements)
references
References 36 publications
20
527
3
8
Order By: Relevance
“…Total radiation treatment time was identified as an important prognostic factor in radiation therapy for cervical cancer since the early 1990s [13]. A total dose of 85 Gy to point A delivered in less than 8 weeks has been accepted as the optimal schedule; the total dose of radiotherapy received by patients in the present study was not different from that of previous studies [1,2,3,4,5]. …”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…Total radiation treatment time was identified as an important prognostic factor in radiation therapy for cervical cancer since the early 1990s [13]. A total dose of 85 Gy to point A delivered in less than 8 weeks has been accepted as the optimal schedule; the total dose of radiotherapy received by patients in the present study was not different from that of previous studies [1,2,3,4,5]. …”
Section: Discussioncontrasting
confidence: 40%
“…Five randomized clinical trials have demonstrated that cisplatin chemotherapy combined with radiotherapy improves PFS and OS in patients with locally advanced cervical cancer [1,2,3,4,5]. The highest dose of cisplatin per cycle was administered in the RTOG study which was the only trial cited in the National Cancer Institute clinical alert to show also a significant decrease in distant relapse [5]; however, no definitive answers about the effect of cisplatin doses combined with radiotherapy on survival are available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the previous trials in patients with cervical cancer, which demonstrated a survival benefit for chemoradiotherapy versus radiotherapy alone [8, 9, 10, 11, 12], Pearcey et al [7]observed similar 3- and 5-year survival rates with concurrent cisplatin and radiotherapy versus radiotherapy alone in patients with advanced cervical carcinoma. While there are many possible explanations for the lack of benefit observed with chemoradiotherapy in this trial, one reason may have been a differential drop in hemoglobin levels during therapy (fig.…”
Section: Studies In Patients With Cervical Cancercontrasting
confidence: 47%
“…In the last few years, several efforts have been made to improve the poor prognosis of patients with locally advanced cervical cancer (LACC), and 5 out of 6 recent clinical trials demonstrated an advantage in terms of disease-free and overall survival in patients treated with concomitant radiation and cisplatin-based chemotherapy [1, 2, 3, 4, 5, 6], which currently represent the gold standard in the treatment of this neoplasia. In addition, among the multimodal treatment strategies attempted, neoadjuvant chemotherapy or chemoradiation followed by radical surgery have also yielded promising results [7, 8, 9, 10].…”
Section: Introductionmentioning
confidence: 99%